Organohalogenated Contaminants in Eggs of Snow Buntings (Plectrophenax nivalis) from Human Settlements in Svalbard - Kristoffersen, Siv (Institutt for biologi, 2012)
Contaminants in the Arctic environment are mainly transported from lower latitude areas by atmospheric transport. However, the Russian settlements (Barentsburg and Pyramiden) in Svalbard have shown to be heavily influenced by local pollution of polychlorinated biphenyls (PCB), as high concentrations have been found in vegetation, soil and sediments. The Norwegian settlements (Longyearbyen and Ny-Ålesund) are to a lesser extent influenced by local pollution of PCB. Birds have been utilized as sentinels for environmental pollution in several studies, as the use of bird-eggs is considered as a non-invasive method. The aim of this study was to investigate whether the snow bunting (Plectrophenax nivalis) is influenced by local pollution of PCB in the Russian settlements. During the 2010 field season and the 2011 field season, 32 eggs of snow buntings were collected in Longyearbyen (n=8), Ny-Ålesund (n=8), Barentsburg (n=9) and Pyramiden (n=7). The analysis was conducted at the Norwegian Institute of Air Research (NILU) in Tromsø. The eggs were analyzed for PCBs, organochlorinated pesticides (OCPs), brominated diphenyl ethers (PBDE) and perfluoroalkylated compounds (PFASs). The results showed that PCBs were the most abundant contaminant group in the Russian settlements, while PFASs was the most abundant contaminant group in the Norwegian settlements. Significant higher concentrations (ng/g wet weigth) of ∑7PCB (sum of the seven most common PCBs) were found in the eggs from the Russian settlements (Barentsburg and Pyramiden) than in the eggs from the Norwegian (Longyearbyen and Ny-Ålesund). Further on, the PCB congener composition in the eggs was comparable with the technical PCB-mixtures previous used in the Russian settlements. The results thus indicate influence of local pollution of PCB in eggs of snow buntings in the Russian settlements. Further on, local influence of dichlorodiphenyldichloroethylene (p,p -DDE) and PFASs cannot be excluded. However, the contaminant burden of hexachlorobenzen (HCB), ...